ANTICORRUPTION EXPERTISE OF LAW-ENFORCEMENT ACTS - S. B. Polyakov (Russian Journal of Economics and Law)
Objective: to substantiate public necessity, to define the subject, methodological and organizational capabilities of anti-corruption expertise of law enforcement acts.Methods: universal dialectic-materialistic method was used to study the needs in anti-corruption expertise of law enforcement acts in the mechanism of legal regulation; based on it, general scientific and special (formal legal and comparative legal) methods of research used for the definition of subject-matter of the proposed expertise.Results: the value of anti-corruption expertise of law enforcement was shown, corruption factors and corruption indicators enabling legislation were identified, ways of conducting such examinations were proposed.Scientific novelty: the article examines the need and the subject, proposes methods of a new type of anti-corruption expertise.Practical significance: the conditions of corruption are defined, which are created in law enforcement activities, and methods for their detec- tion are proposed.